(untitled) (Proceedings of the World Conference on Media and Mass Communication, 2023)
The Vietnamese media is set up to report by frequently bringing up agenda items or events in an effort to sway the public, policymakers, and politicians. Policymakers and governments have subsequently made changes in policy to suit reality, especially the pressing public health issues of natural disasters. Agenda setting refers to the practice of setting the topics for public discourse through the mass media. The purposeful coverage of current events has a significant impact on agenda shaping in terms of how the public views public policies. The media also provides information to decision-makers, enabling them to gather facts and develop helpful policies and initiatives for society. It also provides answers to the queries raised by the general audience. In this study, the content and data of Vietnam’s national television station VTV as well as two well-known domestic newspapers, namely Tuoi Tre and Thanh Nien newspapers, are analyzed using the processes of content analysis and agenda setting theory. Through an analysis of news and television about health and disaster management activities like preparedness, response, and recovery, this study aims to examine how the media gather and shape news to distribute and present it during the typhoon season in Central Vietnam in 2020 in order to determine whether progressive policies reported by the Vietnamese media are actually effective in disaster prevention. Our results, which demonstrate a compelling communication agenda, underline the media’s significant contributions to social issues relating to disaster response and recovery. However, this study also shows that the media has not played its important role in protecting the public health of the affected people before, during, and after the disaster.